A Rational Biphasic Tailoring Strategy Enabling High‐Performance Layered Cathodes for Sodium‐Ion Batteries. (11th March 2022) - Cheng, Zhiwei; Fan, Xin‐Yu; Yu, Lianzheng; Hua, Weibo; Guo, Yu‐Jie; Feng, Yi‐Hu; Ji, Fang‐Di; Liu, Mengting; Yin, Ya‐Xia; Han, Xiaogang; Guo, Yu‐Guo; Wang, Peng‐Fei
Abstract: Layered oxide cathodes usually exhibit high compositional diversity, thus providing controllable electrochemical performance for Na‐ion batteries. These abundant components lead to complicated structural chemistry, closely affecting the stacking preference, phase transition and Na + kinetics. With this perspective, we explore the thermodynamically stable phase diagram of various P2/O3 composites based on a rational biphasic tailoring strategy. Then a specific P2/O3 composite is investigated and compared with its monophasic counterparts. A highly reversible structural evolution of P2/O3–P2/O3/P3–P2/P3–P2/Z/O3′–Z/O3′ based on the Ni 2+ /Ni 3.5+, Fe 3+ /Fe 4+ and Mn 3.8+ /Mn 4+ redox couples upon sequential Na extraction/insertion is revealed. The reduced structural strain at the phase boundary alleviates the phase transition and decreases the lattice mismatch during cycling, endowing the biphasic electrode a large reversible capacity of 144 mAh g −1 with the energy density approaching 514 Wh kg −1 . Abstract : A rational biphasic tailoring strategy to prepare layered composite cathodes with the desired phase ratio is proposed. Benefiting from the reversible phase transition within transition metal slabs and the decreased structure strain at the phase boundary of the intergrowth structure during Na extraction and insertion, the Com‐NaNMFT composite material demonstrates excellent electrochemical performance.